Review: The impact of social and economic change on domesticated plant diversity with special reference to wet rice field and home-garden farming of West Java, Indonesia - JOHAN ISKANDAR; BUDIAWATI S. ISKANDAR; RUHYAT PARTASASMITA (Biodiversitas Journal of Biological Diversity, 2018)
.Iskandar J, Iskandar BS, Partasasmita R. 2018. Review: The impact of social and economic change on domesticated plant diversity with special reference to wet rice field and home-garden farming of West Java, Indonesia. Biodiversitas 19: 565-577. The Impact of social and economic change on genetic diversity of domesticated plants with special reference to wet rice field and home-garden farming of West Java. Various farming systems have played an important role as sources of genetic diversity in plants. A large number of cultivated varieties have been commonly selected, maintained, and distributed by farmers and cultural practices and ecological factors have been involved. These factors, such as soil, climate, pests, and culinary, magical and ritual uses, have influenced farmers in their selection of plants in farming systems. Nowadays, however, the number of plant varieties in various farming systems of Java has dramatically declined. This article attempts to discuss the impact of social and economic change on the genetic diversity of agricultural plants of the wet rice field and home-garden farming, particularly based on data from West Java.